Perbandingan Klaim Penyakit Katastropik Peserta Jaminan Kesehatan Nasional di Provinsi DKI Jakarta dan Nusa Tenggara Timur - Heniwati, Heniwati; Thabrany, Hasbullah (Jurnal Ekonomi Kesehatan Indonesia, 2016)
Several diseases that become catastrophic at the household level include end-stage renal disease, cardiovascular diseases, cancer, thalassemia, and hemophilia. Patients with these diseases benefit significantly from the National Health Insurance (JKN), and these conditions absorb high claim costs from JKN. Special attention is needed to manage these diseases effectively. Disparities in healthcare facilities, specialists, and variations in Case Mix Group (CMG) payment are suspected to be important contributing factors to the variation in JKN fund absorption across provinces. This study uses 2014 claim data from BPJS Kesehatan in Jakarta and East Nusa Tenggara (NTT) provinces to explore the extent of these differences. The total number of claims analyzed was 309,301. The results show statistically significant differences in claim payments per case, per admission, and per hospital day. These differences are primarily due to variations in CMG prices, which do not provide adequate incentives for specialists to work in smaller hospitals of classes B, C, and D in lower-income provinces. This study does not prove the transfer of JKN funds from NTT to Jakarta.